2022
DOI: 10.7554/elife.82228
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1, -2, and -3 motors use family-specific mechanochemical strategies to effectively compete with dynein during bidirectional transport

Abstract: Bidirectional cargo transport in neurons requires competing activity of motors from the kinesin-1, -2 and -3 superfamilies against cytoplasmic dynein-1. Previous studies demonstrated that when kinesin-1 attached to dynein-dynactin-BicD2 (DDB) complex, the tethered motors move slowly with a slight plus-end bias, suggesting kinesin-1 overpowers DDB but DDB generates a substantial hindering load. Compared to kinesin-1, motors from the kinesin-2 and -3 families display a higher sensitivity to load in single-molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…These features confer a distinct advantage during intracellular transport because they increase the probability that when a motor detaches from the microtubule it will rapidly reengage to continue transport. A recent study that tethered kinesin-1 and kinesin-3 motors to dynein-dynactin-BicD2 complexes found that KIF1A could compete against dynein nearly as effectively as kinesin-1, despite their different load-dependent off-rates ( 59 ). Importantly, a computational model that incorporated slow (5 s −1 ) ( 58 , 60 ) reattachment rates for KIF1A and kinesin-1 was unable to recapitulate the data, but if the reengagement rates were set to 990 s −1 for KIF1A and to 100 s −1 for kinesin-1 from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These features confer a distinct advantage during intracellular transport because they increase the probability that when a motor detaches from the microtubule it will rapidly reengage to continue transport. A recent study that tethered kinesin-1 and kinesin-3 motors to dynein-dynactin-BicD2 complexes found that KIF1A could compete against dynein nearly as effectively as kinesin-1, despite their different load-dependent off-rates ( 59 ). Importantly, a computational model that incorporated slow (5 s −1 ) ( 58 , 60 ) reattachment rates for KIF1A and kinesin-1 was unable to recapitulate the data, but if the reengagement rates were set to 990 s −1 for KIF1A and to 100 s −1 for kinesin-1 from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A single dynein-dynactin-BICD2 (DDB) complex has the potential to successfully resist one kinesin module [ 56 ]. When both kinesin and dynein are stepping simultaneously on the MTs and are engaged in competing activity, the kinesin-1, -2 and -3 motors are observed to overpower the hindering forces exerted by the DDB complex via innate mechanochemical strategies and bias the overall cargo movement toward the plus-end [ 57 ]. The dynein light chain TCTEX1 has been reported to associate with the mitochondria via interactions with voltage-dependent anion selective channel 1 in the outer mitochondrial membrane [ 58 ].…”
Section: Mt-mediated Axonal Traffickingmentioning
confidence: 99%
“…We extended the mathematical model developed by Müller et al (40) to simulate the motility of a cargo driven by any number of different types of motors (see Methods). We estimated motor parameters such as binding rate, detachment rate, detachment force, stall force, forward and backward velocities based on previous single-molecule experiments and published models, following closely the analysis in (41) (see methods). To simulate different vesicle populations, we used estimates of the number of motors on each of these cargoes from previous single-molecule fluorescence and quantitative photobleaching experiments (42).…”
Section: Mathematical Modeling Reveals the Estimated Fraction Of Inhi...mentioning
confidence: 99%